2005
DOI: 10.1111/j.1365-2850.2005.00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions of the working environment: a UK independent sector study

Abstract: The working environment is an important determinant of employee well-being. Previous UK studies report registered nurses' perception of the working environment using the Work Environment Scale (WES), but surprisingly few include data for nurses working in mental health or learning disability settings. One hundred and sixty-one (58.8%) registered nurses working day shifts in five specialist divisions (forensic adult mental health, adolescent mental health, elderly continuing care, adult and adolescent learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…This result evidence matches that of Dickens reported that nurse's characterized their work environment by relatively high levels of support, cohesion and managerial control but slightly lower levels of autonomy [18]. Consequently, the influence nurses have and the control they can exert over their practice has been linked to nurse satisfaction.…”
Section: Discussionsupporting
confidence: 76%
“…This result evidence matches that of Dickens reported that nurse's characterized their work environment by relatively high levels of support, cohesion and managerial control but slightly lower levels of autonomy [18]. Consequently, the influence nurses have and the control they can exert over their practice has been linked to nurse satisfaction.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have shown that quality of care is related to staff's well-being [50] and job satisfaction [51,52] The staff that indicated they had greater time to perform their duties also perceived the quality in the secure-environment dimension as higher in this study. This finding is in line with Bowers et al [53], who found that time available for giving care has an impact on quality of care.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, multiple and complex care predominates in nursing care and has been described by nurses to be stressful and emotionally demanding (Hibbert, 1995). In addition, nurses are different in their identifi cation of stressors especially with the complex and frequently changing healthcare environment such as ICUs (Berland, Natvig, & Gunderson, 2008;So & Chan, 2004), emergency departments (ER) (Adeb-Saeedi, 2002;Jonsson & Halabi, 2006), ORs, and Psychiatric Units (Albion, Fogarty, & Machin, 2005;Dickens, Sugarman, & Rogers, 2005;Pinikahana & Happell, 2004;Reininghaus, Craig, Gournay, Hopkinson, & Carson, 2007;Sundin, Hockwalder, Bildt, & Lisspers, 2007).…”
Section: Perception Of Stress and Stressorsmentioning
confidence: 97%